2021
DOI: 10.3390/antibiotics10050493
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping and Antimicrobial Resistance Profile of Enteric Nontyphoidal Salmonella Recovered from Febrile Neutropenic Patients and Poultry in Egypt

Abstract: A total of 300 human fecal samples were collected from febrile neutropenic patients suffering from severe gastroenteritis, followed by identification and serological characterization of recovered isolates. Fifty nontyphoidal Salmonella (NTS) serovars were recovered. A total of serologically identified 50 NTS serovars recovered from poultry of the same geographical area and during the same period as well as one standard strain S. Poona were supplied by the Bacterial Bank of Animal Health Research Institute of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…The results of antibiotic susceptibility testing are illustrated in (Table 2 ); the recovered NTS isolates showed 100% resistance to clindamycin, followed by streptomycin (98.85). These results are consistent with those obtained by many previous studies [ 15 , 24 ] and It was observed that 100% of isolates from both animals and humans were resistant to clindamycin, although its use in large animals was limited. This demonstrated the cross-transmission of NTS between humans and animals (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of antibiotic susceptibility testing are illustrated in (Table 2 ); the recovered NTS isolates showed 100% resistance to clindamycin, followed by streptomycin (98.85). These results are consistent with those obtained by many previous studies [ 15 , 24 ] and It was observed that 100% of isolates from both animals and humans were resistant to clindamycin, although its use in large animals was limited. This demonstrated the cross-transmission of NTS between humans and animals (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The invA gene is considered a universal genetic marker identified in most Salmonella serovars [ 32 ]. Our results confirmed 100% occurrence of invA gene in the examined isolates, as recorded in many previous studies [ 15 , 33 , 34 , 35 ]. However, only 67% of the examined samples were invA gene positive [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on our eligibility criteria, six studies targeted ARGs among Salmonella and Campylobacter as foodborne illnesses in the Middle East region [46][47][48][49][50][51]. Besharati's study and Youssef's study were two studies that reported the ARGs among NTS.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, NTS are the extremely prevalent cause of acquired foodborne infection in humans, causing salmonellosis ( Esmael et al, 2021b ). Salmonellosis is transmitted in humans through the oral-fecal route by the consumption of contaminated food either of animal origin (milk, meat, poultry, and eggs) or green vegetables contaminated by manure ( Youssef et al, 2021 ). The infection symptoms include diarrhea, fever, vomiting, abdominal crumbs as well many other symptoms which arise one or two days after infection and can be persisted for a week ( Wilson and Wilson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%